Traditional three-dimensional printing technology versus three-dimensional printing mirror model technology in the treatment of isolated acetabular fractures: a retrospective analysis - Yu, Cong (J Int Med Res, 2020)
OBJECTIVE: This study was performed to compare the clinical outcomes of traditional three-dimensional (3D) printing technology and 3D printing mirror model technology in the treatment of isolated acetabular fractures. METHODS: Prospectively maintained databases were reviewed to retrospectively compare patients with an isolated acetabular fracture who were treated with traditional 3D printing technology (Group T) or 3D printing mirror model technology (Group M) from 2011 to 2017. In total, 146 advanced-age patients (146 hips) with an isolated acetabular fracture (Group T, n = 72; Group M, n = 74) were assessed for a mean follow-up period of 29 months (range, 24–34 months). The primary endpoint was the postoperative Harris hip score (HHS). The secondary endpoints were the operation time, intraoperative blood loss, fluoroscopy screening time, fracture reduction quality, and incidence of postoperative complications at the final follow-up. RESULTS: The HHS, operation time, intraoperative blood loss, fluoroscopy screening time, and incidence of postoperative complications were significantly different between the groups, with Group M showing superior clinical outcomes. CONCLUSION: In patients with an isolated acetabular fracture, 3D printing mirror model technology might lead to more accurate and efficient treatment than traditional 3D printing technology.